Two new endemic species of blueberry (Vaccinium L., Ericaceae) from Luzon and Mindanao islands, Philippines - Tamayo, Maverick N.; Fritsch, Peter W. (Phytotaxa, 2022)
Two new species of Vaccinium from the Philippines are described and illustrated from historical herbarium collections. Vaccinium burburan from Luzon Island, Northern Philippines is morphologically similar to V. tenuipes, but is distinguished by having shorter petioles, pedicels and corolla, adaxially pubescent leaf blades with cordate base, apically pubescent corollas, and pubescent filaments throughout. It is only one of two species of Vaccinium in the Philippines known to have a cordate leaf blade base. Vaccinium burburan is considered critically endangered. Vaccinium jubatum from Mindanao Island, Southern Philippines, is morphologically similar to V. sylvaticum, but is distinguished by having a dentate leaf blade margin, shorter inflorescences and pedicels, a glabrous calyx, and shorter filaments. The dentate leaf blade margin of V. jubatum uniquely distinguishes it from other Philippine Vaccinium species. The conservation status of V. jubatum is considered data deficient. These discoveries further increase the current number of known Vaccinium species in the Philippines to 40.